F-prostanoid receptor regulation of inflammation in endometrial adenocarcinoma - Wallace, Alison E. (The University of Edinburgh, 2010)
Endometrial adenocarcinoma is the most common gynaecological malignancy in Western countries, affecting mainly post-menopausal women with a frequency of 15-20 per 100 000 women per year. Over-expression of the cyclooxygenase (COX) enzymes and prostaglandin receptors has been demonstrated in endometrial adenocarcinoma as well as other gynaecological pathologies. Increased expression of the prostaglandin F2α (PGF2α) receptor (FP) has been previously demonstrated in endometrial adenocarcinoma. A role for the FP receptor in the promotion of endometrial adenocarcinoma has been shown, with evidence for elevated PGF2α-FP signalling up-regulating angiogenic and tumourigenic genes, and increasing proliferation and migration of neoplastic epithelial cells. This thesis examines signalling pathways regulated by and interacting with the FP receptor that influence chemokine expression and subsequent effects in endometrial adenocarcinoma. To investigate PGF2α-FP interactions in endometrial adenocarcinoma, an endometrial epithelial cell line of adenocarcinoma origin (Ishikawa cells) stably transfected with the FP receptor to levels seen in cancer was used (FPS cells). An antibody array identified the chemokine C-X-C motif Ligand 1 (CXCL1) as a target gene regulated by PGF2α-FP signalling in this cell line. Expression of CXCL1 and its receptor, CXCR2, were elevated in cancer tissue as compared to normal endometrium and localised to glandular epithelium, endothelium and stroma. The induction of CXCL1 expression in FPS cells and endometrial adenocarcinoma explants was determined to be by a signalling pathway involving Gq, the epidermal growth factor receptor (EGFR) and extracellular signal-regulated kinase (ERK). The infiltration of immune cells into endometrial adenocarcinoma as compared to normal endometrium was then investigated. Increased neutrophils were present in endometrial adenocarcinoma compared with normal endometrium, and the expression of CXCR2 was colocalised to neutrophils. In vitro chemotaxis assays demonstrated that conditioned media from PGF2α-treated FPS cells stimulated human neutrophil chemotaxis which could be abolished by CXCL1 protein immunoneutralisation from the conditioned media or antagonism of CXCR2 on neutrophils. Moreover, xenograft tumours in nude mice arising from inoculation with FPS cells had higher neutrophil infiltration compared to tumours arising from wild-type cells or following treatment of mice bearing FPS tumours with CXCL1-neutralising antibody. Therefore, the up-regulation of CXCL1 by PGF2α promoted neutrophil chemotaxis into endometrial adenocarcinoma. The expression of a further chemokine, CC motif Ligand 20 (CCL20) was determined to be regulated by PGF2α -FP signalling in endometrial adenocarcinoma, and expression of CCL20 and its receptor CCR6 was elevated in endometrial adenocarcinoma. The induction of CCL20 by PGF2α -FP signalling in FPS cells was dependent on the signalling molecules Gq, EGFR, ERK, calcineurin and nuclear factor of activated T-cells (NFAT). The treatment of endometrial epithelial cells with recombinant CCL20 caused a significant increase in proliferation. Finally interactions between the signalling pathway of another pro-inflammatory lipid, lysophosphatidic acid (LPA), and FP receptor signalling in endometrial adenocarcinoma were examined. LPA increased expression of the FP receptor and the FP target genes previously discussed in this thesis, CXCL1 and CCL20, in FPS cells. Expression of the LPA receptors (LPAR) 1, 2 and 3 was localised in endometrial tissue, and LPAR2 and 3 were found to be elevated in endometrial adenocarcinoma compared with normal endometrium, suggesting amplification of the PGF2α -FP signalling pathway by LPA was possible. Collectively, these data demonstrate that inflammatory cytokine signalling pathways regulated by PGF2α-FP activation can promote immune cell infiltration and proliferation of endometrial adenocarcinoma, and that interaction of LPA and PGF2α-FP signalling in endometrial adenocarcinoma may exacerbate the disease.
Keywords: endometrial cancer; inflammation; cytokines